Business Development Strategy in Enhcreasing Economic Independence - Hidayatullah, Aldi; Mahmudah, Mahmudah; Qoriani, Hersa Farida (The Es Economics and Entrepreneurship, 2025)
This research has the aim, firstly to explorebusiness entity development strategy in increasing the economic independence of the Darul Hidayah Islamic boarding school, second analyzing the development of business entities in increasing the economic independence of the Darul Hidayah Islamic boarding school, third evaluating the development of business entities in increasing economic independence. The purpose of this study was achieved by a qualitative approach with a descriptive type. Data was obtained by means of observation, interviews and tracing data through the documentation process. The analysis used SWOT analysis (Strengths, Weaknesses, Opportunities, Threaths). Through this process, this study produced the first development strategy carried out with development centered on asatidz, strengthening the operations of the Islamic boarding school, economic development for alumni. Second, its application was carried out in building partnerships, business mentoring, and institutional development. Third, development evaluation in financial evaluation was carried out by means of customer evaluation that emphasized customer satisfaction and evaluation of innovation and learning processes. Innovation based on improving the quality and quality of all elements involved in the process of developing Islamic boarding school-owned business entities.